2022
DOI: 10.1177/01902725221077075
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Tendencies and Subjective Well-Being: A Cross-Cultural Comparison of the United States and Japan

Abstract: Help-seeking is commonly conceived as an instrumental behavior that improves people’s subjective well-being. However, most findings supporting a positive association between help-seeking and subjective well-being are observed in independence-preferring countries. Drawing from research demonstrating that the pathways to subjective well-being are culturally divergent, we posit that help-seeking tendencies may be detrimental to subjective well-being for members in interdependence-preferring countries where norms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…For example, in Lal and Adair's [44] literature review of 115 articles about e-mental health interventions, it was highlighted that digital mental health interventions allow individuals who are uncomfortable with in-person treatment to receive help anonymously and bypass discomforts associated with identifying themselves and facing negative social evaluations. This may be especially helpful for people from collectivist cultures with prevalent "face" concerns, where conventional help-seeking has been found to be associated with poorer life satisfaction and lower positive affect [58]. Moreover, Wies et al's [50] review of 26 digital mental health treatments revealed that apps could serve as an initial point of contact and gradually facilitate transition to faceto-face interventions.…”
Section: Combat Stigma In Help-seekingmentioning
confidence: 99%
“…For example, in Lal and Adair's [44] literature review of 115 articles about e-mental health interventions, it was highlighted that digital mental health interventions allow individuals who are uncomfortable with in-person treatment to receive help anonymously and bypass discomforts associated with identifying themselves and facing negative social evaluations. This may be especially helpful for people from collectivist cultures with prevalent "face" concerns, where conventional help-seeking has been found to be associated with poorer life satisfaction and lower positive affect [58]. Moreover, Wies et al's [50] review of 26 digital mental health treatments revealed that apps could serve as an initial point of contact and gradually facilitate transition to faceto-face interventions.…”
Section: Combat Stigma In Help-seekingmentioning
confidence: 99%
“…The fewer demonological explanations a society has for mental illnesses and disorders, the better individuals respond toward professional help. Lua et al (2022) stated help-seeking behaviors to be related to life satisfaction, with different affects for different societies based on how well individuals adapt to the sensitive perspective of the community to which they've migrated. Bryant et al (2021) posited individuals' mental health to be related to living arrangement, sexuality, age, sense of belonging, and ethnicity.…”
Section: Introductionmentioning
confidence: 99%